Isolation of proteins related to the Rh polypeptides from nonhuman erythrocytes. - Saboori, A M (1989)
It is thought that the Rh antigens may be important in maintaining normal erythrocyte membrane integrity. Despite their name, Rh antigens are serologically present only on human erythrocytes. Rh structural polymorphisms are known to reside within a family of nonglycosylated Mr 32,000 integral membrane proteins that can be purified by hydroxylapatite chromatography. Mr 32,000 integral membrane proteins were purified similarly from erythrocyte membrane vesicles prepared from rhesus monkeys, cows, cats, and rats, but could not be purified from human Rhmod erythrocytes, a rare syndrome lacking Rh antigens. The purified Mr 32,000 polypeptides were labeled with 125I, digested with chymotrypsin, and found to be 30-60% identical to human Rh polypeptides when compared by two-dimensional iodopeptide mapping. The physiologic function of the Rh polypeptides remains to be identified; however, the existence of related proteins in nonhuman erythrocytes supports the concept that the Rh polypeptides are erythrocyte membrane components of fundamental significance.